2006
DOI: 10.1007/s10551-005-4664-5
|View full text |Cite
|
Sign up to set email alerts
|

‘The Impact of Corporate Ethical Values and Enforcement of Ethical Codes on the Perceived Importance of Ethics in Business: A Comparison of U.S. and Spanish Managers’

Abstract: This two country study examines the effect of corporate ethical values and enforcement of a code of ethics on perceptions of the role of ethics in the overall success of the firm. Additionally, the impact of organizational commitment and of individual variables such as ethical idealism and relativism was examined. The rationale for examining the perceived importance of the role of ethics in this manner is to determine the extent to which the organization itself can influence employee perceptions regarding ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
105
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 31 publications
(33 reference statements)
9
105
0
4
Order By: Relevance
“…These findings are consistent with those of previous researchers who found that the correlation between EC and OC was positive and significant (Hunt et al, 1989;Kelley & Dorsch, 1991;Verbeke et al, 1996;Trevino et al, 1998;Singhapakdi et al, 1999;Babin et al, 2000;Schwepker, 2001;Oz, 2001;Valentine et al, 2002;Cullen et al, 2003;Vitell & Hidalgo, 2006;Tsui & Huang, 2008;Shafer, 2009;Zehir et al, 2011;Purhanudin et al, 2012).…”
Section: 00supporting
confidence: 92%
“…These findings are consistent with those of previous researchers who found that the correlation between EC and OC was positive and significant (Hunt et al, 1989;Kelley & Dorsch, 1991;Verbeke et al, 1996;Trevino et al, 1998;Singhapakdi et al, 1999;Babin et al, 2000;Schwepker, 2001;Oz, 2001;Valentine et al, 2002;Cullen et al, 2003;Vitell & Hidalgo, 2006;Tsui & Huang, 2008;Shafer, 2009;Zehir et al, 2011;Purhanudin et al, 2012).…”
Section: 00supporting
confidence: 92%
“…As such, concerned beneficiaries may find the study as a useful means in coming up with the possible solutions for related problems. Through [39]. However, most of these studies were conducted internationally and did not specifically examine the mediating influence of conflict management styles on the relationship between ethical climate and organizational commitment, which is the prime concern of this study, making this dissertation a contribution to the literature for local setting and a means for the generation of new knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that social consensus had the greatest effect on judgments of moral concern and judgments of immorality, and that socio-cultural differences were moderated by the type of ethical issue. In a similar vein, Vitell and Hidalgo (2006) found that the perceived importance of business ethics and social responsibility varied depending upon country of residence, with a US sample showing somewhat higher perceived importance of ethics and social responsibility than a similarly constructed sample in Spain. The authors concluded that companies of American national origin show higher levels of ethicality than the Spanish companies.…”
Section: Introductionmentioning
confidence: 76%
“…The kind generalizations about levels of ethicality in specific national contexts that have been made in some of the studies cited above would seem too broad to be true for any nation. Apart from the fact that the findings cited above (see Vitell and Hidalgo, 2006) beg the question why firms from all national origins, including American, have at various times been accused of unethical practices both at home and in their foreign subsidiaries, greater reported importance of business ethics may be a function of a variety of factors, including the national business system and practices and the level of regulation. Such differences may also be an artefact of the research instrument, and do not necessarily imply more ethical behaviour or even greater ethical awareness.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation